Multiple risk factors for diabetes mellitus in patients with chronic pancreatitis: A multicentre study of 1117 cases. Issue 4 (May 2020) - Olesen, Søren S; Poulsen, Jakob L; Novovic, Srdan; Nøjgaard, Camilla; Kalaitzakis, Evangelos; Jensen, Nanna M; Engjom, Trond; Tjora, Erling; Waage, Anne; Hauge, Truls; Haas, Stephan L; Vujasinovic, Miroslav; et al.
Background: Diabetes mellitus is a common complication of chronic pancreatitis. It is traditionally considered to develop as a consequence of beta cell loss, but there might be additional factors. Recent studies have highlighted the importance of type 2 diabetes-related risk factors in this context and population-based studies show increased risk of diabetes following acute pancreatitis. The aim of this study was to explore multiple risk factors for diabetes in patients with chronic pancreatitis. Methods: We conducted a multicentre, cross-sectional study of patients with definitive chronic pancreatitis according to the M-ANNHEIM criteria. We used multivariable logistic regression models to determine risk factors independently associated with diabetes. Results: The study included 1117 patients of whom 457 (40.9 %) had diabetes. The mean age was 52.8 ± 14.2 years and 67% were men. On multivariate analysis, parameters indicative of beta cell loss (pancreatic calcification, exocrine insufficiency, pancreatic resection) were confirmed as independent risk factors for diabetes (all p ≤ 0.02). In addition, type 2 diabetes-related risk factors (dyslipidaemia and overweight/obesity) were associated with the presence of diabetes (all p ≤ 0.002). Patients with a history of pancreatic fluid collections (indicative of previous attacks of acute pancreatitis) had a marginally increased risk of diabetes ( p = 0.07). Conclusion: In patients with chronic pancreatitis the presence of diabetes is associated with multiple risk factors including type 2 diabetes-related factors. Our observations attest to the understanding of this entity and may have implications for treatment.